A study of women's representation in relation to poverty: a case study of The Post March 2009 - Gwanvalla, Delphine Ngehndab (Rhodes University, Faculty of Humanities, School of Journalism and Media Studies, 2013)
The media, specifically tabloids, have the potential to portray poverty-related issues in a manner that informs the public and government about the experiences of people living in poverty so that it can be tackled with urgency. Poverty has blighted the lives of many, especially women, children and widows in Cameroon. The role of the media in reporting the plight and suffering of the 'masses' potentially shapes the way in which these issues are handled by those in authority. The study notes that the tabloid press has the potential to expose certain experiences of ordinary people thereby constituting that alternative sphere for the disadvantaged. The study investigates the manner women are represented in The Post which is an English tabloid published in Cameroon. The representation of women in this study looks at the institutional policies which drive the representation of women in news constructs, analyses the news values which shape news production, and uses Thompson's modes of ideology to unravel the underlying meanings in the reported stories. The study is inspired by the claims that since women make up the majority of the world's poor, so too would media representations depict them as such. It utilises thematic analysis to understand the manner in which women are represented in The Post. It also uses interviews with the regional bureau editor of the North West region to probe what news values and institutional policies drive the stories on women's poverty. Document analysis is used to better comprehend the institutional guidelines which govern the representation of women during the month of March 2009.
Keywords: Journalism, Commercial -- Social aspects -- Cameroon; Women -- Cameroon -- Social conditions; Poor women -- Cameroon; Mass media and women -- Cameroon